Effectiveness of the selected techniques in enhancing the achievement in science among the children with learning disabilities: sharing experiences - Hamzah, Mohd Sahandri Gani; Subramaniam, Vijayaletchumy; Abdullah, Saifuddin Kumar (David Publishing Company, 2009)
In national perception, education is essentially for all. This is fundamental to all-round development, material and spiritual. It refines sensitivities and perceptions that contribute to national cohesion, a scientific temper and independence of mind and spirit-thus furthering the goals of socialism secularism and democracy enshrined in our constitution. The objective of the study focuses on achievement of children with learning disability in science. There are 5 null hypothesis tested in this research. The sample used in this study includes 35 children with learning disabilities in experimental group and 42 children with learning disabilities in control group. The different views taken on special education have ignited spark of controversies over segregating some children from the mainstream and providing them with extra opportunities. There are arguments for and against both special education and integrated education. Special education means the specifically designed instruction that meets the unusual needs of special children. It requires special materials, teaching, techniques, equipment and facilities. The design was an experimental research pre and post-test equivalent group. The research shows that there is no significant difference in all learning objective such as knowledge, comprehension and skill between control group and experimental group in the pre-test. This two sample groups also did not show any significant difference in the pre-test irrespective of gender, educational qualification of the teacher, years of experience of the teacher, parents' education, parents' profession, parents income, type of management and type of school. On the other hand, for the post-test all the characteristics show that there are significant differences. This shows that there are effects on the treatment group in learning objective. Furthermore the experimental group showed significantly higher gain score than the control group with regard to the learning objective which comprises of knowledge, comprehension, application and skill.